FUNGSI KOMUNIKASI ORGANISASI DALAM PENERAPAN WFH PADA KARYAWAN SWASTA SELAMA PANDEMI COVID-19 - Davis Roganda Parlindungan (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Since the Covid-19 pandemic broke out in Indonesia, most of the affected companies have tried to limit the space for activities in the office and change the work system of their employees to work more from home or, in other terms, the Work From Home (WFH) work system to reduce the risk of transmission. Covid-19 virus. The purpose of this study is to describe how the function of organizational communication in implementing the WFH work system that occurs to employees, especially in private companies in Jakarta during the Covid-19 pandemic. The qualitative research approach collects data from interviews, observations, and literature studies. The results of the study illustrate that since the implementation of the WFH work system during the Covid-19 pandemic, the informative, regulatory, persuasive, and integrative organizational communication functions for employees have continued to run but have encountered various obstacles, such as the informative function relies heavily on online media communication in disseminating, discussing and provide work instructions between superiors and subordinates. The regulatory function is still considered less than optimal by employees regarding eligibility criteria, means of communication, and compensation for employees who have to work full time from the office. Likewise, the leadership's persuasive function is still not running, especially in making immediate decisions and monitoring the quality and discipline of employees. Meanwhile, the integrative communication function is carried out entirely through the internet.